Effects of Organic Polymer Compound Material on K+ and Na+ Distribution and Physiological Characteristics of Cotton Under Saline and Alkaline Stresses - Wang, Xiaoli; An, Mengjie; Wang, Kaiyong; Fan, Hua; Shi, Jiaohua; Chen, Kuan (Frontiers in Plant Science, 2021)
Soil salinization and alkalization are the environmental factors that greatly restrict crop growth and yield. In this study, NaCl (8 g kg-1) and Na2CO3 (8 g kg-1) were used to create saline stress and alkaline stress on cotton in pot cultivation in the field, and modifier and stem girdling were applied before cotton sowing and at flowering and boll-forming stage, respectively, aiming to determine the effects of modifier on K+ and Na+ absorption and transport and physiological characteristics of cotton leaf and root. The results showed that the Na+ content in leaf and root were decreased by the application of modifier under saline and alkaline stresses, and the K+/Na+ ratio and K+ and Na+ transport coefficients of leaf-stem were increased. The activities of superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD), and relative electrical conductivity (REC) in cotton leaf were significantly increased, and the content of malondialdehyde (MDA) was decreased; but the changes in those in root were not significant. The boll weight for cottons under saline and alkaline stresses were significantly increased compared with that for the control. After stem girdling, the application of modifier still increased the ion transport of cotton organs, and also increased the activities of SOD and CAT in leaf and root. Therefore, modifier can significantly change the transport mechanism of K+ and Na+ to maintain the K+ and Na+ homeostasis in leaf and root,, and regulate physiological and biochemical indicators to alleviate the stress-induced damage. Besides, the regulation effect of modifier on saline stress was better than that on alkaline stress.